Offset-fed Slotted Antenna Practically Loaded with Split Ring as Water Quality Sensor for X-Band Industrial Applications - A. Varshney; D. N. Gençoğlan (Advanced Electromagnetics, 2024)
This article communicates an offset-fed split ring loaded slotted-antenna design, testing, and analysis for different water quality sensor. The antenna was designed to resonate at 10GHz on a low-cost FR-4 substrate of dimensions 0.621λo×0.467λo×.053λo, where λo is the free space wavelength. The measured antenna parameters are found in excellent agreements. The antenna achieves a gain of 7.61dBi with nearly unidirectional radiation pattern and a radiation efficiency of 76% at 10GHz. Further, the research is explored to use the antenna as a water sample sensor. Different water samples are tested with the antenna by dipping the antenna into the water samples and in the second case contactless measurements at 10mm apart from the upper water level in the container. The quality of water is examined by observing the shift in the resonant frequency (fr), antenna quality factor with different total dissolved solvents (TDS) water samples, and changes in the reflection coefficient (S11) values in the water samples. It is observed that the antenna shows less than 1.5% numerical sensitivity (NS) with fr and high NS with the S11. The S11 and bandwidth of the antenna vary with different water samples. This antenna is suitable for X-band industrial and microwave laboratory applications.